Reactively sputtered WO3 thin films for the application in all thin film electrochromic devices. (20th December 2019) - Pan, Lijun; Han, Qiaonan; Dong, Zhongliang; Wan, Meixiu; Zhu, Hongbing; Li, Yang; Mai, Yaohua
Abstract: In this study, tungsten trioxide (WO3 ) thin films were prepared at different working pressures by direct current (DC) reactive magnetron sputtering for the application in all thin film electrochromic devices (ATF-ECDs). The target voltage was used to monitor the target status and employed as an advanced technology to choose process parameter set for special working points in particular for reactive magnetron sputtering of transition metal oxides here. Various properties of WO3 thin films including deposition rate, optical property, chemical composition, crystal structure, morphology, electrochemical properties as well as electrochromic property were systematically investigated. In addition, the device performances of the ATF-ECDs including optical modulation, coloration efficiency, switch time and stability were investigated as well. The ATF-ECDs with WO3 thin films sputtered at 4.0 Pa showed a high optical modulation (TT at 600 nm) of up to 70.9% and a relatively fast switch time (2 s for bleaching step and 13 s for coloring step) as well as a better cycle stability.